An analytical review on application of life cycle assessment in circular economy for built environment. (December 2021) - Lei, Haoran; Li, Le; Yang, Wei; Bian, Yadong; Li, Chun-Qing
Abstract: Built environment, also referred to as the product of construction industry, has exerted tremendous impact on the natural environment. Circular economy aims to decouple the environmental burden from economic growth and promotes a circular built environment. Adopting life cycle assessment in circular economy can avoid extra environmental impact due to increased circularity. This paper intends to analytically review the applications of life cycle assessment in circular economy for the built environment. The necessity of incorporating life cycle assessment in circular economy is highlighted. It is found in the review that adoption of life cycle assessment enhances the comprehensiveness and transparency of circular economy implementation in the built environment. To overcome the inherent limitations of life cycle assessment methods that hinder their applications in circular economy, practitioners need to constantly improve the consistency of functional unit and system boundary, the accessibility and quality of life cycle inventory data as well as the reliability of impact allocation methods. It is also found that dynamic life cycle assessment that considers the time factor can increase the applicability of life cycle assessment in circular economy. The main contribution of this review is a proposal for the transition of the built environment towards a circular and sustainable future. Highlights: Review on applications of life cycle assessment in circular economy for built environment. Adoption of life cycle assessment enhances the comprehensiveness and transparency. Practitioners need to constantly improve the consistency of functional unit and system boundary. Dynamic life cycle assessment can increase the applicability of LCA in circular economy. A proposal for the transition of the built environment towards a circular and sustainable future.